Price of pulse oximeters bought by the students of pharmacy faculty - Brytanova, T. S.; Antypenko, L.; Британова, Тетяна Сергіївна (Tokyo : CPN Publishing Group, 2022)
Aim. The analysis of pulse oximeter pharmaceutical market situation [3] to prevent the Covid-19 consequences using pulse oximeters is still strongly relevant.